Association Between Egg Consumption and Dementia Risk in the EPIC-Spain Dementia Cohort - Margara-Escudero, Hernando J.; Zamora-Ros, Raul; de Villasante, Izar; Crous-Bou, Marta; Chirlaque, María-Dolores; Amiano, Pilar; Mar, Javier; Barricarte, Aurelio; Ardanaz, Eva; Huerta, José María (Frontiers in Nutrition, 2022)
Background Current evidence suggests that egg composition might have potential neuroprotective effects. Our aim was to determine the association between egg consumption and the risk of dementia in a Mediterranean population. Methods This study was carried out in 3 centers from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Spain Dementia Cohort, i.e., 25,015 participants aged 30–70 years, recruited in 1992–1996, and followed up for a mean of 21.5 years. Results A total of 774 incident dementia cases were diagnosed and validated, of which 518 were Alzheimer's disease (AD). Data on egg consumption were estimated using a validated dietary history questionnaire at recruitment. Cox proportional hazards models, adjusted for confounders, were used in the analyses. No association was observed between egg consumption and either total dementia [hazard ratio between extreme quartiles (HRQ4vs.Q1: 1.05; 95% CI 0.85–1.31; p-trend = 0.93)] or AD (HRQ4vs.Q1 0.93; 95% CI 0.72–1.21; p-trend = 0.50) risks. After dividing the population by adherence to the relative Mediterranean diet (rMED) score, a borderline inverse association was found between egg intake and both total dementia (HRQ4vs.Q1: 0.52; 95% CI 0.30–0.90; p-trend = 0.10) and AD (HRQ4vs.Q1: 0.52; 95% CI 0.27–1.01; p-trend = 0.13) risks within participants with low adherence to rMED score. However, no association was observed in participants with medium and high adherence to rMED score. Conclusion This prospective study suggests that egg consumption is associated with a reduced risk of dementia, and specifically of AD, in the adult population with low adherence to rMED score; whereas it has no impact in subjects with moderate and high MD adherence.